A high-strength aluminum alloy material and preparation method thereof
By forming multi-walled nanocarbon tubes loaded with SiNxOy in the aluminum matrix, the problem of poor bonding between the reinforcement and the metal matrix is solved, significantly improving the mechanical properties and wear resistance of the aluminum alloy material, and achieving high strength and tensile resistance. promote.
Patent Information
- Application Number
- CN202411472665.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-22
AI Technical Summary
In the existing particulate reinforced aluminum-based composite materials, the reinforcement body and the metal matrix have poor bonding and uneven distribution, resulting in insufficient mechanical properties of the material.
By forming SiNxOy-loaded multi-walled carbon tubes in the aluminum matrix as nanoreinforcing agents, fine and stable reinforcement particles are formed through chemical reactions, improving the mechanical properties of the material and enhancing the bond between the reinforcement and the matrix.
It significantly improves the tensile strength, hardness and wear resistance of the material, improves the dispersion rate of nano-carbon tubes and the combination with the matrix, and achieves high strength and wear resistance technical effects.
Smart Images

Figure CN118979181B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of alloy materials, and specifically relates to a high-strength aluminum alloy material and a preparation method thereof. Background Art
[0002] Aluminum has excellent thermal conductivity, electrical conductivity, corrosion resistance and ductility, and can be enhanced by adding alloy elements and heat treatment to meet different needs. High-strength aluminum alloy material is an alloy material with excellent strength. This material is usually subjected to a special heat treatment process to make it have higher strength and hardness while maintaining good machinability and corrosion resistance. High-strength aluminum alloy materials are widely used in aerospace, automobiles, ships, construction and other fields to meet the requirements of material strength and lightweight. Common high-strength aluminum alloy materials include 7075 aluminum alloy, 2024 aluminum alloy and 6061 aluminum alloy. Carbon nanotubes are a new type of self-assembled single-molecule material with a strength of about 100 times that of steel and a density of only 1 / 6 of that of steel. They are materials with very high specific strength and specific stiffness. Recent studies have found that adding an appropriate amount of carbon nanotubes as a reinforcement to metal-based composites can improve the strength and wear resistance of the material; the in-situ self-generation method can form ceramic particles with small size, regular shape, high stiffness and good interface bonding with the matrix in the aluminum alloy matrix. The in-situ particle-reinforced aluminum-based composite material has high specific strength, specific stiffness, low thermal expansion coefficient and good wear resistance, and therefore the particle size is small, the thermal stability is good, and the interface is clean and pollution-free.
[0003] The existing technology currently has the following main problems: the current particle-reinforced aluminum-based composite materials have poor bonding between the reinforcement and the metal matrix and uneven distribution. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a high-strength aluminum alloy material and a preparation method thereof. In order to solve the problems of poor bonding and uneven distribution between the reinforcement and the metal matrix, the present invention proposes to obtain a nano-reinforcement agent in the form of multi-walled carbon nanotubes loaded with SiNxOy, and form small and stable reinforcement particles in the aluminum matrix through chemical reaction, thereby achieving the improvement of the mechanical properties of the material and the good bonding of the multi-walled carbon nanotubes with the aluminum-based alloy, thereby further improving the mechanical properties of the material.
[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: The present invention proposes a high-strength aluminum alloy material and a preparation method thereof, wherein the high-strength aluminum alloy material comprises the following components in weight percentage: Zn 5-6%, Mg 2-2.5%, Cu 1.5-1.8%, Fe 0.3-0.4%, Si 0.08-0.1%, Cr 0.2-0.25%, Ti 0.03-0.05%, Mn 0.01-0.03%; the balance is Al, nano-reinforcement agent and unavoidable impurities;
[0006] Preferably, the content of the nano-enhancer is 1.2-2wt% of the total mass of the alloy material;
[0007] Preferably, the nano-enhancer is a multi-walled carbon nanotube loaded with SiNxOy;
[0008] Preferably, the mass fraction of N in the SiNxOy is 30% to 34%, the mass fraction of O is 30% to 36%, and the particle size range is 20-30nm;
[0009] Preferably, the preparation method of the nano-enhancer comprises the following steps:
[0010] S1, adding multi-walled carbon nanotubes to 65-70wt% concentrated nitric acid, condensing and refluxing at 60°C for 6h, standing, filtering, washing, and drying to obtain acidified carbon nanotubes;
[0011] S2, adding 3-aminopropyltriethoxysilane to an oxalic acid solution with a pH of 4 to obtain a coupling agent solution, mixing the acetone solution with the coupling agent solution to obtain a mixed solution, adding SiNxOy to the mixed solution, ultrasonically dispersing, and standing at 30° C. for 24 h; centrifuging, washing, and drying to obtain modified SiNxOy;
[0012] S3. Add the acidified carbon nanotubes obtained in S1 into deionized water, disperse by ultrasonic, add the modified SiNxOy obtained in S2, disperse by magnetic stirring for 4 h, react at 100° C. for 6 h, wash and dry to obtain the nano-enhancer.
[0013] SiNxOy nanopowder can easily interact with Al. The reaction between SiNxOy and Al in the nanoreinforcement during sintering is as follows:
[0014] (3x+2y)Al+3SiNxOy→3Si+3xAlN+yAl2O3;
[0015] Aluminum can also reduce SiNxOy to silicon dioxide. Silicon dioxide and AlN have good chemical compatibility. Below 1400°C, no chemical reaction occurs between the two phases.
[0016] Preferably, in S1, the amount of the multi-walled carbon nanotubes added to 65-70wt% concentrated nitric acid is 8-10 mg / mL.
[0017] Preferably, in S1, the amount of 3-aminopropyltriethoxysilane added to the oxalic acid solution at pH 4 is 18-22 mg / mL.
[0018] Preferably, in S2, the amount of SiNxOy added to the acetone solution is 28-38 mg / mL.
[0019] Preferably, in S2, the volume ratio of the coupling agent solution to the acetone solution is 1:55-60.
[0020] Preferably, in S3, the amount of the acidified carbon nanotubes added to the deionized water is 0.6-0.8 mg / mL.
[0021] Preferably, in S3, the amount of the modified SiNxOy added is 3-5 times the mass of the acidified carbon nanotubes.
[0022] The present invention also provides a high-strength aluminum alloy material and a preparation method thereof, which specifically comprises the following steps:
[0023] The nano-reinforcement agent is uniformly mixed with Zn, Mg, Cu, Fe, Si, Cr, Ti, Mn and Al, subjected to high-energy ball milling treatment, and then subjected to spark plasma sintering treatment to obtain a high-strength aluminum alloy material.
[0024] Preferably, in the high-energy ball milling, the mass ratio of ZrO2 balls to powder mixture is 1:0.08-0.1, and the mixture is mixed at a rotation speed of 800-1000 rpm for 20-30 min in an Ar atmosphere.
[0025] Preferably, in the spark plasma sintering, the applied pressure is 30-40 MPa, the heating rate is 30-40° C. / min, the sintering temperature is 630-660° C., and the sintering temperature holding time is 10-15 min.
[0026] The beneficial effects achieved by the present invention are as follows: multi-walled carbon nanotubes are acidified and modified to generate carboxyl groups on their surfaces to obtain acidified carbon nanotubes; SiNxOy is modified by a silane coupling agent to allow 3-aminopropyltriethoxysilane and its bonding material to carry amino groups, so that the amino groups generated by 3-aminopropyltriethoxysilane-modified SiNxOy and the carboxyl groups generated by acidification of the multi-walled carbon nanotube surfaces are combined with each other to form amide bonds to obtain multi-walled carbon nanotubes with SiNxOy loaded on the surface, namely, nano-enhancers; the nano-enhancers are mixed with metal powders for ball milling and sintering; the carbon nanotubes are more evenly dispersed during the sintering process due to the SiNxOy loaded on the surface; SiNxOy reacts with Al to generate aluminum nitride, aluminum oxide and part of silicon dioxide; fine and stable reinforcing particles are formed in an aluminum matrix through chemical reactions, which not only strengthens the material but also improves the dispersion rate of the multi-walled carbon nanotubes and enhances their bonding with the matrix, thereby improving the mechanical properties of the material and achieving the technical effects of high strength, tensile strength and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The tensile strength test results of Examples 1-3 and Comparative Examples 1-4 are shown in FIG.
[0028] Figure 2 The results of the tensile test elongation at break of Examples 1-3 and Comparative Examples 1-4 are shown in FIG.
[0029] Figure 3 The results of the hardness test of Examples 1-3 and Comparative Examples 1-4 are shown in FIG.
[0030] Figure 4 The graph is a result of the wear test of Examples 1-3 and Comparative Examples 1-4.
[0031] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0034] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0035] Example 1
[0036] A high-strength aluminum alloy material includes the following weight percentage components: Zn6%, Mg2.5%, Cu1.8%, Fe0.4%, Si0.1%, Cr0.25%, Ti0.05%, Mn0.03%; the balance is Al, nano-reinforcement agent and inevitable impurities;
[0037] The content of the nano-reinforcement agent is 2wt% of the total mass of the alloy material; the nano-reinforcement agent is a multi-walled carbon nanotube loaded with SiNxOy; the mass fraction of N in SiNxOy is 34%, the mass fraction of O is 36%, and the particle size range is 30nm.
[0038] The preparation method of the nano-enhancer specifically comprises the following steps:
[0039] S1, adding multi-walled carbon nanotubes in an amount of 10 mg / mL to 70 wt% concentrated nitric acid, condensing and refluxing at 60° C. for 6 h, standing, filtering, washing, and drying to obtain acidified carbon nanotubes;
[0040] S2. Add 3-aminopropyltriethoxysilane in an amount of 22 mg / mL to an oxalic acid solution with a pH of 4 to obtain a coupling agent solution, mix the acetone solution and the coupling agent solution in a volume ratio of 1:60 to obtain a mixed solution, add SiNxOy in an amount of 38 mg / mL to the mixed solution, disperse by ultrasonication, and stand at 30°C for 24 hours; centrifuge, wash, and dry to obtain modified SiNxOy;
[0041] S3. Add the acidified carbon nanotubes obtained in S1 to deionized water at an amount of 0.8 mg / mL, disperse by ultrasonic, add the modified SiNxOy obtained in S2 in an amount 5 times the mass of the acidified carbon nanotubes, disperse by magnetic stirring for 4 h, react at 100° C. for 6 h, wash and dry to obtain the nano-enhancer.
[0042] The present invention also provides a high-strength aluminum alloy material and a preparation method thereof, which specifically comprises the following steps:
[0043] The nano-reinforcement agent is uniformly mixed with Zn, Mg, Cu, Fe, Si, Cr, Ti, Mn and Al, and subjected to high-energy ball milling treatment. The mass ratio of ZrO2 ball to powder mixture is 1:0.1. The mixture is mixed at a speed of 1000 rpm in an Ar atmosphere for 30 minutes, and then subjected to spark plasma sintering treatment. The applied pressure is 40 MPa, the heating rate is 40°C / min, the sintering temperature is 660°C, and the sintering temperature holding time is 15 minutes to obtain a high-strength aluminum alloy material.
[0044] Example 2
[0045] A high-strength aluminum alloy material includes the following weight percentage components: Zn5%, Mg2%, Cu1.5%, Fe0.3%, Si0.08%, Cr0.2%, Ti0.03%, Mn0.01%; the balance is Al, nano-reinforcement agent and inevitable impurities;
[0046] The content of the nano-reinforcement agent is 1.2wt% of the total mass of the alloy material; the nano-reinforcement agent is a multi-walled carbon nanotube loaded with SiNxOy; the mass fraction of N in SiNxOy is 30%, the mass fraction of O is 30%, and the particle size range is 20nm.
[0047] The preparation method of the nano-enhancer specifically comprises the following steps:
[0048] S1, adding 8 mg / mL of multi-walled carbon nanotubes to 65 wt% concentrated nitric acid, condensing and refluxing at 60° C. for 6 h, standing, filtering, washing, and drying to obtain acidified carbon nanotubes;
[0049] S2. Add 3-aminopropyltriethoxysilane in an amount of 18 mg / mL to an oxalic acid solution with a pH of 4 to obtain a coupling agent solution, mix the acetone solution and the coupling agent solution in a volume ratio of 1:55 to obtain a mixed solution, add SiNxOy in an amount of 28 mg / mL to the mixed solution, disperse by ultrasonication, and stand at 30°C for 24 hours; centrifuge, wash, and dry to obtain modified SiNxOy;
[0050] S3. Add the acidified carbon nanotubes obtained in S1 into deionized water at an amount of 0.6 mg / mL, disperse by ultrasonic, add the modified SiNxOy obtained in S2 in an amount 3 times the mass of the acidified carbon nanotubes, disperse by magnetic stirring for 4 h, react at 100° C. for 6 h, wash and dry to obtain the nano-enhancer.
[0051] The present invention also provides a high-strength aluminum alloy material and a preparation method thereof, which specifically comprises the following steps:
[0052] The nano-reinforcement agent is uniformly mixed with Zn, Mg, Cu, Fe, Si, Cr, Ti, Mn and Al, and subjected to high-energy ball milling treatment. The mass ratio of ZrO2 ball to powder mixture is 1:0.08. The mixture is mixed at a rotation speed of 800 rpm in an Ar atmosphere for 20-30 minutes, and then subjected to spark plasma sintering treatment. The applied pressure is 30 MPa, the heating rate is 30°C / min, the sintering temperature is 630-660°C, and the sintering temperature holding time is 10-15 minutes to obtain a high-strength aluminum alloy material.
[0053] Example 3
[0054] A high-strength aluminum alloy material includes the following weight percentage components: Zn5.5%, Mg2.2%, Cu1.6%, Fe0.35%, Si0.09%, Cr0.22%, Ti0.04%, Mn0.02%; the balance is Al, nano-reinforcement agent and inevitable impurities;
[0055] The content of the nano-reinforcement agent is 1.8wt% of the total mass of the alloy material; the nano-reinforcement agent is a multi-walled carbon nanotube loaded with SiNxOy; the mass fraction of N in SiNxOy is 32%, the mass fraction of O is 33%, and the particle size range is 25nm.
[0056] The preparation method of the nano-enhancer specifically comprises the following steps:
[0057] S1, adding multi-walled carbon nanotubes in an amount of 9 mg / mL to 68 wt% concentrated nitric acid, condensing and refluxing at 60° C. for 6 h, standing, filtering, washing, and drying to obtain acidified carbon nanotubes;
[0058] S2, adding 3-aminopropyltriethoxysilane in an amount of 20 mg / mL to an oxalic acid solution with a pH of 4 to obtain a coupling agent solution, mixing the acetone solution and the coupling agent solution in a volume ratio of 1:56 to obtain a mixed solution, adding SiNxOy in an amount of 30 mg / mL to the mixed solution, ultrasonically dispersing, and standing at 30°C for 24 hours; centrifuging, washing, and drying to obtain modified SiNxOy;
[0059] S3. Add the acidified carbon nanotubes obtained in S1 to deionized water at an amount of 0.7 mg / mL, disperse by ultrasonic, add the modified SiNxOy obtained in S2 in an amount of 3-5 times the mass of the acidified carbon nanotubes, disperse by magnetic stirring for 4 hours, react at 100°C for 6 hours, wash and dry to obtain the nano-enhancer.
[0060] The present invention also provides a high-strength aluminum alloy material and a preparation method thereof, which specifically comprises the following steps:
[0061] The nano-reinforcement agent is uniformly mixed with Zn, Mg, Cu, Fe, Si, Cr, Ti, Mn and Al, and subjected to high-energy ball milling treatment. The mass ratio of ZrO2 ball to powder mixture is 1:0.09. The mixture is mixed at a speed of 900 rpm in an Ar atmosphere for 25 minutes, and then subjected to spark plasma sintering treatment. The applied pressure is 35 MPa, the heating rate is 35°C / min, the sintering temperature is 640°C, and the sintering temperature holding time is 13 minutes to obtain a high-strength aluminum alloy material.
[0062] Comparative Example 1
[0063] This comparative example provides an aluminum alloy material, which differs from Example 1 only in that the components do not contain a nano-reinforcement agent, and the remaining components and component contents are the same as those of Example 3.
[0064] Comparative Example 2
[0065] This comparative example provides an aluminum alloy material, which differs from Example 1 only in that the components do not contain nano-carbon tubes, and the remaining components and component contents are the same as those of Example 3.
[0066] Comparative Example 3
[0067] This comparative example provides an aluminum alloy material, which differs from Example 1 only in that SiNxOy is not included in the composition, and the other components and component contents are the same as those in Example 3.
[0068] Comparative Example 4
[0069] This comparative example provides an aluminum alloy material, which differs from Example 1 only in that no nano-reinforcement agent is prepared, that is, the nano-carbon tubes and SiNxOy are simply mixed, and the remaining components and component contents are the same as those in Example 3.
[0070] Experimental example
[0071] 1. Tensile test
[0072] The materials obtained in Examples 1-3 and Comparative Examples 1-4 were subjected to a tensile test using an electronic stretching machine. The stretching speed was 0.8 mm / min. Each group of samples was stretched three times. The environmental chamber was first set to 25°C, and the samples were placed in the chamber for 10 minutes before being stretched to obtain the tensile strength and elongation at break.
[0073] 2. Hardness test
[0074] The materials obtained in Examples 1-3 and Comparative Examples 1-4 were made into test blocks of 10 mm × 10 mm × 10 mm, and the surfaces of the samples were polished clean with sandpaper. The microhardness of the samples was tested with a 1600–5122VD MICROMET5104 microhardness tester. Eight points were measured for each sample, the experimental load was 50 g, the holding time was 15 s, and the average was taken as the sample hardness.
[0075] 3. Wear test
[0076] The materials obtained in Examples 1-3 and Comparative Examples 1-4 were made into Φ35mm×4mm discs, and a certain positive pressure was applied to press the steel ball at the bottom of the pin onto the surface of the aluminum alloy disc to be tested. The motor was started to make the steel ball and the disc to be tested slide relative to each other. The mass before and after the friction and wear test was tested using an electronic balance, and the wear amount was calculated using the following formula:
[0077] Wear amount = mass before test - mass after test
[0078] Results Analysis
[0079] 1. Tensile strength
[0080] Figure 1 The tensile strength results of the tensile tests of Examples 1-3 and Comparative Examples 1-4 are shown in the figure. As shown in the figure, the tensile strengths (MPa) of Examples 1-3 and Comparative Examples 1-4 are 776, 779, 787, 436, 539, 543, and 603, respectively. The tensile strength of Example 1-3 is significantly stronger than that of Comparative Example 1-3, indicating that the use of nano-reinforcers, carbon nanotubes, and SiNxOy improves the tensile strength of the alloy material. The tensile strength of Example 1-3 is significantly stronger than that of Comparative Example 4, indicating that the preparation of nano-reinforcers improves the tensile strength of the alloy material, which is better than simple mixing.
[0081] 2. Elongation at break
[0082] Figure 2 The result graph of the elongation at break of the tensile test of Example 1-3 and Comparative Example 1-4 is as shown in the figure. The elongation at break of Example 1-3 and Comparative Example 1-4 are 23.1%, 22.7%, 23.5%, 10.8%, 16.1%, 15.3% and 19.3%, respectively; the elongation at break of Example 1-3 is significantly higher than that of Comparative Example 1-3, indicating that the use of nano-reinforcement agent, carbon nanotubes and SiNxOy improves the elongation at break of the alloy material. The elongation at break of Example 1-3 is significantly higher than that of Comparative Example 4, indicating that the preparation of nano-reinforcement agent improves the elongation at break of the alloy material, which is better than simple mixing.
[0083] 3. Hardness
[0084] Figure 3The hardness test result of Examples 1-3 and Comparative Examples 1-4 is shown in the figure. As shown in the figure, the hardness of Examples 1-3 and Comparative Examples 1-4 are 195Hv, 196Hv, 197Hv, 130Hv, 156Hv, 153Hv, and 172Hv, respectively. The hardness of Example 1-3 is significantly greater than that of Comparative Example 1-3, indicating that the use of nano-reinforcement agent, carbon nanotubes, and SiNxOy improves the hardness of the alloy material. The hardness of Example 1-3 is significantly greater than that of Comparative Example 4, indicating that the preparation of nano-reinforcement agent improves the hardness of the alloy material, which is better than simple mixing.
[0085] 4. Wear
[0086] Figure 4 The wear test results of Examples 1-3 and Comparative Examples 1-4 are as follows. As shown in the figure, the hardnesses of Examples 1-3 and Comparative Examples 1-4 are 6.5, 6.3, 6.7, 12.3, 9.2, 9.5, and 7.8, respectively; the wear amount of Example 1-3 is significantly lower than that of Comparative Example 1-3, indicating that the use of nano-reinforcers, nano-carbon tubes, and SiNxOy improves the wear resistance of the alloy material. The wear amount of Example 1-3 is significantly lower than that of Comparative Example 4, indicating that the preparation of nano-reinforcers improves the wear resistance of the alloy material, which is better than simple mixing.
[0087] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
[0088] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A high-strength aluminum alloy material, Features: The composition includes the following weight percentages: Zn 5-6%, Mg 2-2.5%, Cu 1.5-1.8%, Fe 0.3-0.4%, Si 0.08-0.1%, Cr 0.2-0.25%, Ti 0.03-0.05%, Mn 0.01-0.03%; the balance is Al, nano-enhancer and unavoidable impurities; The content of the nano-enhancer is 1.2-2wt% of the total mass of the alloy material; The nano-enhancer is a multi-walled carbon nanotube loaded with SiNxOy; The mass fraction of N in the SiNxOy is 30-34%, the mass fraction of O is 30-36%, and the particle size range is 20-30 nm.
2. A method for preparing the high-strength aluminum alloy material according to claim 1, Features: Specifically, the method comprises the following steps: uniformly mixing the nano-reinforcement agent with Zn, Mg, Cu, Fe, Si, Cr, Ti, Mn and Al, performing high-energy ball milling treatment, and then performing spark plasma sintering treatment to obtain a high-strength aluminum alloy material; The high energy ball milling, ZrO 2 The mass ratio of the ball to powder mixture was 1:0.08-0.1, and the mixture was mixed at 800-1000 rpm in an Ar atmosphere for 20-30 min; The spark plasma sintering has an applied pressure of 30-40 MPa, a heating rate of 30-40° C. / min, a sintering temperature of 630-660° C., and a sintering temperature holding time of 10-15 min.
3. The method for preparing the high-strength aluminum alloy material according to claim 2, Features: The preparation method of the nano-enhancer specifically comprises the following steps: S1, adding multi-walled carbon nanotubes to 65-70wt% concentrated nitric acid, condensing and refluxing at 60°C for 6h, standing, filtering, washing, and drying to obtain acidified carbon nanotubes; S2, adding 3-aminopropyltriethoxysilane to an oxalic acid solution with a pH of 4 to obtain a coupling agent solution, mixing the acetone solution with the coupling agent solution to obtain a mixed solution, adding SiNxOy to the mixed solution, ultrasonically dispersing, and standing at 30° C. for 24 hours; centrifuging, washing, and drying to obtain modified SiNxOy; S3. Add the acidified carbon nanotubes obtained in S1 into deionized water, disperse by ultrasonic, add the modified SiNxOy obtained in S2, disperse by magnetic stirring for 4 h, react at 100° C. for 6 h, wash and dry to obtain the nano-enhancer.
4. The method for preparing the high-strength aluminum alloy material according to claim 3, Features: In S1, the amount of the multi-walled carbon nanotubes added to 65-70wt% concentrated nitric acid is 8-10 mg / mL.
5. The method for preparing the high-strength aluminum alloy material according to claim 4, Features: In S1, the amount of 3-aminopropyltriethoxysilane added to the oxalic acid solution with a pH of 4 is 18-22 mg / mL.
6. The method for preparing the high-strength aluminum alloy material according to claim 5, Features: In S2, the amount of SiNxOy added to the acetone solution is 28-38 mg / mL.
7. The method for preparing the high-strength aluminum alloy material according to claim 6, Features: In S2, the volume ratio of the coupling agent solution to the acetone solution is 1:55-60.
8. The method for preparing the high-strength aluminum alloy material according to claim 7, Features: In S3, the amount of the acidified carbon nanotubes added to the deionized water is 0.6-0.8 mg / mL.
9. The method for preparing the high-strength aluminum alloy material according to claim 8, Features: In S3, the amount of the modified SiNxOy added is 3-5 times the mass of the acidified carbon nanotubes.
Citation Information
Patent Citations
Alumina-fiber-reinforced ceramic materials and production process thereof
CA2086435A1
Dispersions for additive manufacturing comprising discrete carbon nanotubes
CA3213250A1
Carbon nanotube and ceramic nanoparticle hybrid reinforced magnesium-based composite material and preparation method thereof
CN106555089A
Crystal whisker oriented reinforcing aluminum-based composite material and preparation method thereof
CN109112439A
Preparation method of carbon nanotube reinforced aluminum-based composite material with surface coated with aluminum oxide
CN110669956A
